PENGARUH PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP HASIL BELAJAR IPS (Studi Eksperimen Kuasi di Kelas IV SDN 032 Kualu Kecamatan Tambang Kabupaten Kampar) - Refina Yuliani; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of the application of learning models talk think write (TTW) to the learning result IPS elementary school fourth grade students of SD Negeri 032 Kualu . This study is a quasi - experimental and research design using a nonequivalent control group design . Its population is the fourth grade students of SD Negeri 032 Kualu . While the sample is a class IV A as a control class with the number of students 35 and class IV B as a class experiment with a number of students to 35 people. The sampling is done by purposive sampling technique . The data of the student learning result is collected using objective test , question the pretest and posttest . The data obtained were analyzed using t-test analysis using microsoft exel 2007. The results showed that there are significant differences between student learning outcomes were studied using model talk think write (TTW) with student learning outcomes studied using model common on subjects IPS . It can be seen from t_hitung > t_tabel or 8.91 > 1,998 , this means that both the mean score of posttest learning outcomes there are significant differences and student learning outcomes in both classes is not the same . Differences were also seen from the average score of the second class , the experimental class gained an pretest average of 62.51 and posttest average of 89.77 and gained control class pretest average of 63.02 and posttest average of 70.37 . Based on correlational test can be obtained great effect the implementation models talk think write (TTW) to the learning outcomes IPS by 40 % while 60 % are influenced by other factors contained in the students themselves and the environment.Keywords: Learning Model Talk Think Write ( TTW ) , Learning Outcomes IPS